COMPARISON OF FLOATING NET CAGES CULTIVATION TECHNIQUES IN JATIGEDE RESERVOIR AND JATILUHUR RESERVOIR: REGULATION, MANAGEMENT, CULTIVATION SYSTEM, AND ENVIRONMENTAL IMPACT - Andriani, Yuli; Lestari, Vira (Universitas Mataram, 2025)
Aquaculture using the Floating Net Cage (FNCs) system has rapidly developed and become an important economic source, but it also poses environmental pressures such as pollution and eutrophication. Jatigede and Jatiluhur Reservoirs serve as examples of water bodies affected by the accumulation of aquaculture waste, despite having different legal statuses and management approaches. This study aims to evaluate the environmental impacts of FNCs aquaculture in both reservoirs and to formulate sustainable management strategies that balance economic and ecological aspects. The findings indicate that FNCs activities are prohibited in Jatigede through local regulations; however, illegal practices persist due to economic reasons, with simple farming systems centered on Nile tilapia. In contrast, Jatiluhur allows FNCs operations under a permit system, but the number of cages has exceeded the environmental carrying capacity, with more intensive farming practices using high levels of supplementary feed. Ecological impacts such as eutrophication occur in both reservoirs, with a more severe scale in Jatiluhur. Sustainable management efforts are urgently needed, including alternative livelihoods, regulation of FNCs numbers, and education on environmentally friendly aquaculture practices.